Delay and probability discounting in cocaine use disorder: Comprehensive examination of money, cocaine, and health outcomes using gains and losses at multiple magnitudes - Cox, David J. (Exp Clin Psychopharmacol, 2019)
Understanding factors associated with cocaine use disorder is important given its public health impact. One factor is delay discounting (devaluation of future consequences). Cocaine-users have shown greater delay discounting of money rewards than non-cocaine-users. But under-examined are factors known to affect discounting, such as sign (reward vs. loss), magnitude (e.g., $10 vs. $1000), and commodity (e.g., money vs. health) of the consequence. Also under-examined is probability discounting (devaluation of uncertain consequences). We conducted a comprehensive group-comparison study of discounting processes by comparing sign, magnitude, and commodity effects between demographically matched cocaine-users (n=23) and never-users (n=24) for delay discounting; and sign and magnitude effects for probability discounting. Participants completed delay and probability discounting tasks spanning: rewards and losses; money, cocaine, and health outcomes; and magnitudes of $10, $100, and $1000. Four primary findings emerged when controlling for other drug use. First, cocaine-users pervasively discounted delayed consequences more than never-users regardless of sign, magnitude or commodity, with the possible exception of delay discounting of $1000 health equivalences. Second, both groups discounted delayed rewards more than losses, with a similar trend for probability discounting. Third, magnitude effects in cocaine-users for delayed and probabilistic outcomes were similar to those previously observed in never-users and other-drug-users. Fourth, cocaine-users discounted cocaine-related outcomes more than money and health, with variable results comparing money and health. These data suggest the behavioral processes of delay and probability discounting are qualitatively similar for cocaine-users and never-users. However, quantitatively, cocaine-users generally show greater delay and similar probability discounting than never-users.